Vihara Dhanagun dan Komunikasi Budaya di Kota Bogor, Jawa Barat - Burhanudin, Dede (Jurnal Lektur Keagamaan, 2018)
This article discusses the Dhanagun Temple, one of the Confucian worship houses in Bogor. Through the study of places of worship, the theme of cultural communication was raised, especially Confucians with the surrounding environment, by revealing the context of the historical setting, which includes the time, founders, and conditions of the community around that time, the architectural model of buildings, and the following philosophical meanings contained in it. Furthermore, it was also revealed that the use of this place of worship in the socio-cultural context from its inception to the present. Dhanagun Temple has dominant characteristics of Chinese architecture. The frame uses a multilevel beam structure system and a beam bond structure system. The shape of the roof stands out with a frame structure system made of wood. This monastery is decorated with ornaments that can be grouped into five categories, namely animals (fauna), plants (flora), nature (universes such as fire, water, and sun), geometrics, and legends, especially about gods. The results of this study are expected to enrich the archipelago's religious treasures, explore the values of local wisdom and conserve and preserve historical heritage, including historic places of worship.Keywords: Dhanagun Temple, culture, history, architecture, ornament.Artikel ini membahas Vihara Dhanagun, salah satu rumah ibadah Konghucu di Bogor. Melalui kajian rumah ibadah ini diangkat tema komuniÂ¬kasi budaya, khususnya penganut Konghucu dengan lingkungan sekitarnya, dengan mengungkap konteks latar sejarah berdirinya, yang meliputi waktu, pendiri, serta kondisi masyarakat di sekitar saat itu, model aristektur bangunan, dan benda-benda berikut makna filosofis yang terkandung di dalamnya. Selin itu, diungkap pula pemanfaatan rumah ibadah ini dalam konteks sosial budaya sejak awal berdirinya sampai saat ini. Vihara Dhanagun memiliki karekteristik arsitektur Tionghoa. Rangkanya menggunakan sistem struktur balok bertingkat dan sistem struktur ikatan balok. Bentuk atapnya menonjol dengan sistem struktur rangka yang terÂ¬buat dari kayu. Vihara ini dihiasi dengan ornamen yang dapat dikelompokkan menjadi lima kategori, yaitu hewan (fauna), tumbuhan (flora), nature (alam semesta seperti api, air, dan matahari), geometrik, dan legenda, terutama tentang dewa-dewa. Dari hasil kajian ini diharapkan dapat menambah khazanah keagamaan Nusantara, menggali nilai-nilai kearifan lokal dan mengkonservasi serta melestarikan peninggalan bersejarah, termasuk rumah ibadah bersejarah.Kata Kunci: Vihara Dhanagun, budaya, sejarah, Arsitektur, ornamen